Understanding the development of self-efficacy for physical activity engagement in men after myocardial infarction: a preliminary qualitative study (Journal) - Abu, Harlinna; Mohamed Ludin, Salizar; Sowtali, Siti Noorkhairina (Journal of Public Health Research, 2021)
Background: This preliminary finding of a qualitative study explored the process of self-efficacy for physical activity development among myocardial infarction (MI) after recovery. A combination of healthy behaviours including physical activity is the secondary prevention recommended to decrease the risk of recurrent MI. Self-efficacy is a term used to describe an individual’s belief that they can put their skills to use, in this case for physical activity, and capable to control their lives despite obstacles and barriers. It is believed that self-efficacy is the determinant factor in adherence to physical activity. Aims: The purpose of the study was to understand how self-efficacy for physical activity developed in a patient after MI by exploring their perceptions and personal adherence to physical activity. Method: This was a qualitative study and data were collected through semi-structured in-depth recorded phone interviews from eight Malay male participants. Participants were screened through questionnaire and participants who met the inclusion criteria were interviewed. The participants were admitted to National Heart Centre, Malaysia between January to June 2019 diagnosed as MI. Data were organized using NVivo 12 software and thematic analysis was applied. Results: Five preliminary themes emerged from the analysed data; 1) Beliefs in physical activity; 2) Healthy lifestyle: New normal or same old habit; 3) Factors determining participation in PA; and 4) Physical activity adherence strategies. Conclusion: The results of the studies showed that participants understand the need for physical activity adherence to helps them to sustain a healthy life after MI and prevent recurrent infarction. Strategies on how they develop the self-efficacy for physical activity also were discussed. The need to understand that physical activity adherence as well as adopting a new normal of healthy habit after MI is crucial to sustain their health and prevent recurrence of MI.